Endometrioid Carcinoma Four Years After Hysterectomy: A Rare Case Report - Rahim, Riffat; Hira, Nahida Akter; Banerjee, Rinita (Mugda Medical College Journal, 2024)
It is quite a fascinating case as we have recently experienced in Mugda Medical College Hospital, a tertiary level teaching hospital in Dhaka, Bangladesh, that a woman was diagnosed and treated for endometrioid adenocarcinoma four years after her vaginal hysterectomy had been done. Our patient was presented with abdominal pain for nearly 2 weeks along with nausea, vomiting and generalized weakness. Ultrasound evaluation revealed a complex pelvic mass (8.6cm × 4.9cm). Chest x-ray revealed a left sided pleural effusion, while CT scan of the abdomen revealed heterogeneously enhancing complex pelvic mass and mild ascites. After a clinical correlation with all the pathological investigations, the patient was advised for a core biopsy. Ultrasonogram guided core biopsy was done. Histopathological examination showed a malignant ovarian epithelial tumor. Then she underwent an interventional or surgical procedure, which included an exploratory laparotomy, bilateral salpingo-oophorectomy with bilateral pelvic lymph node dissection and infracolic omentectomy done under general anesthesia. The final histopathological examination of the removed mass showed an endometrioid adenocarcinoma (Grade 2). Meanwhile, she was referred for radiation therapy (both vaginal brachytherapy and external pelvic radiation) after the patient had recovered from surgery. We will discuss this case as a part of our clinical interest and continuing education for our clinicians and residents. Mugda Med Coll J. 2024; 7(1): 53-55